Online Shopping Experience and Customer Satisfaction: Evidence from Zamfara Central Senatorial District (UNIZIK Journal of Marketing, 2024)
This study examines the relationship between online shopping experience and customer satisfaction in Zamfara Central Senatorial District.  A survey research design was used to generate data from online shoppers and retailers and was analyzed using IBM SPSS, version 26 to test the hypotheses.  Technology acceptance model anchored for online shoppers and retailers for various online tools for shopping. Data was collected from 286 sample sizes from online shoppers and retailers using a structured questionnaire.  Findings found that online shopping had the greatest influence and there is a significant effect of online customer satisfaction for online shopping. Hence the study recommends online shoppers and retailers should prioritize customer satisfaction based on usability, hedonic, pragmatic, website design, website quality, product variety, and customer support to enhance the e-SQ elements that would lead to an improved sense of trust, loyalty, enjoyment security, time delivery of service and security experience and customer satisfaction
Keywords: Usability experience; Pragmatic experience; Hedonic experience; Customer satisfaction